Fermentados de fungos filamentosos como potencial fonte de nutracêuticos para aplicação na nutrição de ruminantes - Conceição, Aparecido Almeida (2022)
Filamentous fungi are able to add value to plant biomass through the production of primary and secondary metabolites. The main objective of this work was to obtain fermented filamentous fungi using different combinations of plant biomass with potential nutraceutical application for use in ruminant nutrition. For this, five filamentous fungi were used in solid state fermentation (FES) of plant biomasses commonly used in Brazilian Midwest as animal feed. The fermented products that presented the best results in terms of growth rate, laccase activity and/or increments of molecules with potential nutraceutical application were evaluated for digestibility and gas production in vitro. The dynamics of protein and secondary metabolites concentration during solid-state fermentation process was also evaluated. The best activities for laccases were observed in P. lecomtei fermented in substrates composed of (grain: whether sorghum, oat or corn) + moringa + pigeon pea, especially the sorghum (ST -12) with 416.8±20.28 U/g. The A. terreus fermented in ST-09 (sorghum+pigean) improved the protein concentration (15.3±0.46%), also showing significant concentrations for β-glucan (503.56±8.6 mg/g) and lovastatin (1.10±0.17 mg/g). As for the in vitro digestibility parameters, the fermented P. lecomtei in CT-11 (corn+rice husk+pigeon) presented the best values of lignin degradation (NDF of 41.08%, ADF of 33.61% and lignin of 9.48%), in vitro gas production (IVGP) of 109.79 mL/g(DM) and dry matter digestibility (DMD) of 67.37%, when compared to the non-fermented substrate. Finally, the quantification of proteins in A. terreus oat grains fermented is related to dry matter loss. The results indicate the potential of fermented products as nutraceuticals for ruminants, however more studies are needed to ensure safety and efficiency in ruminant nutrition in vivo.